Growing Native Medicinal Plants in Amajari – RR (International Seven Journal of Multidisciplinary, 2024)
The aim of this work was to set up a permanent production area for native and exotic medicinal plants, especially those at risk of extinction. The species grown were herbs, shrubs and medicinal trees of various species, both native and exotic. Nineteen species were cultivated by 20 students from the Ovídio Dias de Souza State School who took part in the practicals at the school. It was observed that the fact that the majority of the students reported a preference for using medicinal plants, perhaps due to the lack of any other way of maintaining or recovering their health, is, in a way, a positive aspect, because as well as strengthening traditional practices regarding the use and traditional knowledge of medicinal plants, it is an activity that values the preservation of the local flora.